Determinants of Profitability at Bank Muamalat Indonesia: The Effect of Murabahah, Mudharabah, Musyarakah, and Ijarah Financing - Desta Meiliya; Faruq Ahmad Futaqi (Falahiya Journal of Islamic Banking and Finance, 2026)
Introduction: This study examines the effect of murabahah, mudharabah, musyarakah, and ijarah financing on the profitability of Bank Muamalat Indonesia during 2015–2024. Profitability is an important indicator in measuring the effectiveness of Islamic bank performance in managing productive assets. However, the increase in financing distribution is not always followed by an increase in profitability, creating a gap between theory and empirical facts. Research Methods: This study uses a quantitative approach with secondary data obtained from Bank Muamalat Indonesia financial reports for the 2015–2024 period. The analysis technique uses multiple linear regression with classical assumption tests, t-test, F-test, and coefficient of determination. Results: The results indicate that murabahah, mudharabah, and musyarakah financing have a positive and significant effect on profitability, while ijarah financing has a negative and significant effect on profitability. Simultaneously, all financing variables significantly affect profitability.Conclusion: Financing management has an important role in improving Islamic bank profitability. Therefore, Islamic banks need to optimize financing quality and operational efficiency to improve financial performance sustainably.